Ecohydrological assessment of densely canalized urban waterways for ecological reconnection and landscape restoration in Lagos metropolis: nexus for human–nature connectivity - Adesina, John Adekunle; Tang, Xiaolan; Ren, Yujie; Jiang, Hongchao; Fuh, Winchester Ndum; Zhang, Ying (Frontiers in Sustainable Cities, 2025)
Urban watershed and drainage infrastructure and networks provide cities with a wide range of benefits, solving a myriad of problems facing urban settlements. Due to the neglect of the wetlands over the years, this study examines the application of hydrological assessment through landscape modeling to uncover environmental problems facing the densely populated Lagos metropolis. Data for the study were collected through direct surveys, remote sensing, and physical observation of the 145.68 km2 study area and green corridor. The adoption of Geographical Information System (GIS) analysis to identify flood direction, peaks, and depressions, as well as watersheds, aims to develop a spatial model that identifies and prioritizes this waterway corridor, thereby improving landscape connectivity within the metropolis. The study obtained topographical data reports using a simple kriging predictor to determine the geostatistics and spatial analysis used to examine rainfall threats, flood hazards, and susceptibility, which was conducted at the community levels following the highlights of six zones. Aligning the study with established Flood Risk Index (FRI) ranging from 0 to 100%, the Urban River Restoration Index (URRIx), ranging from 0 to 1 and flood factor risk score ranging from 1 to 10 which shows that whenever it is equal to zero (on the scale of 0–1), there are no risk and threat whatsoever and 1/10 risk score indicates that there are minimal risk. The continuous decrease in watershed biodiversity due to an increase in anthropogenic activities has disrupted the integrity of habitats and the environmental sustainability of the metropolis, as well as areas susceptible to high flood impacts. The conclusion called for immediate restoration action by policymakers, stakeholders, and researchers to prioritize waterways for sustainable development and metropolitan transitioning, considering the findings that maintaining a balance between human–nature connectivity in urban areas where natural ecosystems are quickly replaced by human activities is worrisome.